MODERN FACTORS OF FORMING INDEPENDENT LEARNING SKILLS IN ENGINEERS USING DIGITAL ELECTRONIC TEXTBOOKS (European Journal of Pedagogical Initiatives and Educational Practices, 2025)
This article presents ideas and considerations about the factors of using digital educational resources, methods of designing tasks, and tools in forming independent learning skills in students.